9, 10-diphenylanthracene (DPA) single crystals grown by conventional slow evaporation method and its characterisation. (28th July 2016) - Muthuraja, A.; Kalainathan, S.
Abstract : Single crystals of 9, 10-diphenylanthracene (DPA) were grown by slow evaporation solution growth technique. The grown crystal was confirmed by single crystal. Powder X-ray diffraction was carried out to confirm the crystallinity of the grown crystal. The percentage of transmittance and lower cut-off wavelength was identified from UV–vis–NIR studies. The thermal characteristics of DPA were analysed by thermogravimetric (TG) and differential thermal analysis (DTA). The mechanical stability of DPA crystal was analysed by Vicker's hardness test. The refractive index of DPA crystal was found to be 1.652. Photoluminescence studies reveal that the DPA crystal exhibits UV light emission. The third-order nonlinear optical property of DPA crystal was analysed through Z-scan technique using He–Ne laser at the wavelength of 632.8 nm. The laser damage threshold value of DPA is found to be 2.18 GW/cm 2 .